2022
DOI: 10.3390/plants11131638
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Biorational Products for Managing Diseases of Tomato in Greenhouse Production

Abstract: Gray mold (Botrytis cinerea), late blight (Phytophthora infestans), powdery mildew (Leveillula taurica), pith necrosis (Pseudomonas corrugata), and bacterial canker (Clavibacter michiganensis) are major diseases that affect tomato (Solanum lycopersicum L.) in greenhouse production in Mexico. Management of these diseases depends heavily on chemical control, with up to 24 fungicide applications required in a single season to control fungal diseases, thus ensuring a harvestable crop. While disease chemical contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The potential for inducing plant defense responses before pathogen infection has not yet been developed to a practical level for cannabis. However, as discussed earlier, Regalia Maxx ( Reynoutria sachalinensis ), when applied to cannabis plants, can reduce pathogens such as B. cinerea and powdery mildew, confirming reports in the literature of the efficacy through presumed induction of defense responses and pathogen reduction [ 63 , 64 , 65 , 66 , 67 ]. Weekly applications are recommended to ensure the ongoing protection of cannabis plants.…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...supporting
confidence: 78%
See 1 more Smart Citation
“…The potential for inducing plant defense responses before pathogen infection has not yet been developed to a practical level for cannabis. However, as discussed earlier, Regalia Maxx ( Reynoutria sachalinensis ), when applied to cannabis plants, can reduce pathogens such as B. cinerea and powdery mildew, confirming reports in the literature of the efficacy through presumed induction of defense responses and pathogen reduction [ 63 , 64 , 65 , 66 , 67 ]. Weekly applications are recommended to ensure the ongoing protection of cannabis plants.…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...supporting
confidence: 78%
“…The active ingredients in Milstop ® (potassium bicarbonate), Cyclone ® (citric and lactic acid), and Suffoil-X ® (mineral oil) are all considered to be ‘physical’ in their mode of action, altering leaf surface pH and osmotic pressure or desiccating/coating mycelium and spores [ 6 ]. The active ingredient in Regalia Maxx ® is an extract from the giant knotweed Reynoutria sachalinensis and was shown to be effective against pathogens such as B. cinerea and powdery mildew on cannabis as well as on various other crops [ 63 , 64 , 65 , 66 ]. This product enhances plant defense responses through the salicylic acid (SA)-dependent pathway by inducing the accumulation of plant defense chemicals such as hydrogen peroxide and the formation of mechanical plant defenses such as callose papillae [ 66 , 67 ].…”
Section: Cannabis Pathogens: Symptoms and Management Approaches At Di...mentioning
confidence: 99%
“…A base soil treatment of Bacillus spp. or B. subtilis combined with foliar-applied Reynoutria sachalinensis , Melaleuca alternifolia , harpin αβ proteins, or bee honey efficiently reduced the intensity of grey mould ( B. cinerea) and powdery mildew ( Leveillula taurica) as compared to conventional foliar disease control [ 148 ]. Mousa et al [ 149 ] showed that B. amyloliquefaciens BA, alone or in combination with peppermint oil, promoted seed germination and seedling vigour and reduced the severity of Fusarium wilt in tomato (pathogen F. oxysporum f. sp.…”
Section: Combined Strategies For Tomato Disease Managementmentioning
confidence: 99%
“…The active ingredients in Milstop ® (potassium bicarbonate), Cyclone ® (citric and lactic acid), and Suffoil-X ® (mineral oil) are all considered to be 'physical' in their mode of action, altering leaf surface pH and osmotic pressure or desiccating/coating mycelium and spores [6]. The active ingredient in Regalia Maxx ® is an extract from the giant knotweed Reynoutria sachalinensis and was shown to be effective against pathogens such as B. cinerea and powdery mildew on cannabis as well as on various other crops [63][64][65][66]. This product enhances plant defense responses through the salicylic acid (SA)-dependent pathway by inducing the accumulation of plant defense chemicals such as hydrogen peroxide and the formation of mechanical plant defenses such as callose papillae [66,67].…”
Section: Application Of Reduced-risk Productsmentioning
confidence: 99%